HIV protease inhibitors restore amphotericin B activity against Candida - Yehia Elgammal; Ehab A. Salama; Mohamed N. Seleem (PLoS ONE, 2025)
Candida auris is an invasive fungal pathogen, representing a global public health threat. It is characterized by high mortality rates among infected individuals, significant antifungal resistance, and a remarkable ability to persist in healthcare environments. While amphotericin B is one of the most powerful antifungal agents for treating Candida infections, approximately 30% of C. auris isolates demonstrate resistance to it. Thus, the development of novel antifungal therapies is vital for tackling its life-threatening infections. In this study, we identified four HIV protease inhibitors (atazanavir, saquinavir, lopinavir and ritonavir) as strong potentiators of amphotericin B against C. auris. A synergistic effect between HIV protease inhibitors and amphotericin B was observed against 15 C. auris isolates with fractional inhibitory concentration index (FICI) ranging from 0.09 to 0.50. Additionally, the combinations between HIV protease inhibitors and amphotericin B showed fungicidal effect, significantly reducing the viable cell count in the time-kill assay within 6 hours. Furthermore, the combinations inhibited biofilm formation of C. auris by 60–75% and exhibited a remarkable suppression of C. albicans hyphae. The in vivo treatment with HIV protease inhibitors combined with amphotericin B resulted in a significant reduction of C. auris colony-forming units (CFU) by 1.7–2.6 Log10 in the C. elegans model. These findings suggest that HIV protease inhibitors, in combination with amphotericin B, are promising candidates for the development of novel antifungal drugs to treat Candida infections.